Penerapan SOP Waiter/waitress terhadap Kualitas Pelayanan untuk Meningkatkan Kepuasan Tamu di Restaurant Peterseli Kitchen - Asur Suryana; Ika Fitria Hasibuan; Sri Febdarina; Dini Ramadhani; Maryantina Maryantina (TOBA: Journal of Tourism, Hospitality, and Destination, 2026)
Service quality is a crucial factor in determining customer satisfaction in the restaurant industry. This study aims to analyze the implementation of waiter/waitress SOPs, service quality, and guest satisfaction at Peterseli Kitchen Restaurant Pekanbaru. This research employed a qualitative descriptive method with data collection techniques through interviews, observations, and questionnaires. Research respondents consisted of 99 restaurant guests, 10 waiters/waitresses, 1 head captain, and 1 manager. Service quality was measured using five SERVQUAL dimensions (Tangible, Empathy, Reliability, Responsiveness, and Assurance), while guest satisfaction was measured through three indicators (meet expectation, repurchase intention, and willing to recommendation) using a 5-point Likert scale. The results showed that the implementation of waiter/waitress SOPs has been carried out very well through 15 consistent operational procedure stages. Service quality obtained an average score of 4.9, which is categorized as very good, with all dimensions showing optimal performance. Guest satisfaction was also in the very satisfied category with an average score of 4.9, indicating that guests have a high interest in making repeat visits and recommending the restaurant to others. This study concludes that the implementation of structured SOPs and strict supervision have a positive effect on service quality and guest satisfaction. It is recommended that the restaurant continues to maintain existing service standards while developing product diversification strategies to expand market segments.